Handbook of air pollution prevention and control - Cheremisinoff, Nicholas P. (Butterworth-Heinemann, 2002)
This Handbook provides a concise overview of the latest technologies for managing industrial air pollution in petrochemical, oil and gas, and allied industries. Detailed material on equipment selection, sizing, and troubleshooting operations is provided along with practical design methodology. Unique to this volume are discussions and information on energy-efficient technologies and approaches to implementing environmental cost accounting measures. Included in the text are sidebar discussions, questions for thinking and discussing, recommended resources for the reader (including Web sites), a.